2021
DOI: 10.1186/s13063-021-05075-1
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up Maternal Mental healthcare by Increasing access to Treatment (SUMMIT) through non-specialist providers and telemedicine: a study protocol for a non-inferiority randomized controlled trial

Abstract: Background Depression and anxiety impact up to 1 in 5 pregnant and postpartum women worldwide. Yet, as few as 20% of these women are treated with frontline interventions such as evidence-based psychological treatments. Major barriers to uptake are the limited number of specialized mental health treatment providers in most settings, and problems with accessing in-person care, such as childcare or transportation. Task sharing of treatment to non-specialist providers with delivery on telemedicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 75 publications
(86 reference statements)
0
50
0
Order By: Relevance
“…We examined reported barriers to accessing in-person healthcare due to COVID-19, perceived barriers that are speci c to the COVID-19 pandemic, and potential facilitators to resuming in-person psychotherapy sessions during COVID-19 speci c to perinatal women with symptoms of depression and anxiety in the context of the SUMMIT trial [20]. One key nding that emerged was perinatal participants and providers reported that perinatal women experienced barriers to accessing healthcare and in-person psychotherapy throughout the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We examined reported barriers to accessing in-person healthcare due to COVID-19, perceived barriers that are speci c to the COVID-19 pandemic, and potential facilitators to resuming in-person psychotherapy sessions during COVID-19 speci c to perinatal women with symptoms of depression and anxiety in the context of the SUMMIT trial [20]. One key nding that emerged was perinatal participants and providers reported that perinatal women experienced barriers to accessing healthcare and in-person psychotherapy throughout the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…SUMMIT, a multi-site, four-arm, randomized, non-inferiority trial, is being conducted across three hubs in . Full details of the SUMMIT trial protocol have been published elsewhere [ 20 ].…”
Section: Study Sites and Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this qualitative study, our primary aim was to examine the barriers that might impact perinatal patients' access to in-person psychotherapy sessions and facilitators to resuming in-person sessions from the perspectives of perinatal patients, providers, and relevant community-and hospital-based stakeholders. The current study was conducted within the Scaling Up Maternal Mental healthcare by Increasing access to Treatment (SUMMIT) trial, which is aimed at increasing access to mental health treatment among perinatal patients with symptoms of depression and anxiety in Canada and the United States by delivering a form of psychotherapy called behavioral activation (BA) [22]. Though a central aim of the SUMMIT trial is to compare whether BA delivered via telemedicine is as effective as when it is delivered in-person, similar to many other clinical research and practices, all perinatal participants in the SUMMIT trial were exclusively randomized to telemedicine beginning in mid-March 2020 due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…For example, women reported feeling less isolated, more con dent as mothers, and more likely to seek or continue with formal mental health support [13][14] . In recognition of the potential of these roles and bene ts, there has been growing international interest and investment in the peer support role across a range of service contexts 12,15 . Despite this, however, the evidence-base on where peer supporters may most effectively t within perinatal mental health service delivery remains unclear.…”
Section: Introductionmentioning
confidence: 99%